Tata Laksana Perioperatif Pembedahan Tiroid : Sebuah Tinjauan Pustaka - Ariobimo, Bonfilio Neltio; Nujum, Nurun; Puspamaniar, Vania Ayu; Saputro, Daniel Ponco Harto (Majalah Kedokteran Indonesia, 2023)
Thyroidectomy is one of the frequently performed surgery worldwide with indications of malignant or benign tumors, or functional abnormalities in thyroid gland. Surgery on the neck is actually a high-risk procedure because it is performed on structures attached to blood vessels, nerves and airways, so adequate perioperative management is warranted. This literature review aims to summarize the latest perioperative management of thyroid surgery. Preoperative management includes control of signs and symptoms of hyperthyroidism or hypothyroidism, fasting, administration of prophylactic antibiotic, and airway management. During surgery, special attentions are needed related the use of anesthetic drugs, hemodynamic monitoring, and efforts to prevent nerve injury. In addition, several postoperative complications that need to be detected and treated early, including hypocalcemia, hematoma, injury of recurrent laryngeal nerve, postoperative pain, nausea, and vomiting, and tracheomalacia. All those perioperative management requires multidisciplinary collaboration.